From Socialist Realism to Postmodern Scepticism: U.R. Ananthamurthy’s Critique of Civil Society - Raghavendra Rao G.S., (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2026)
This article examines the intellectual evolution of Kannada writer U.R. Ananthamurthy, tracing his transition from the “Socialist Realist” optimism of the Pragatisheela movement to a “Postmodern Scepticism” regarding the Indian state and its civil society. Central to this critique is Ananthamurthy’s portrayal of the “English-educated elite” as an administrative and secular vanguard that inadvertently perpetuates a “Colonial Consciousness”. By analyzing the failure of the bureaucrat Satisha in Bara and the rationalist Jagannatha in Bharathipura, the study illustrates how top-down modernity often performs “epistemic violence” against the very subjects it seeks to liberate. Drawing on Ashis Nandy’s theories of the “Intimate Enemy” and S.N. Balagangadhara’s critique of Western categorical dominance, the article argues that Ananthamurthy moves toward a Linguistic Democracy. This model rejects the Upstairs language (Attada Mathu) of the state in favour of the pluralistic, Critical Insider perspective found within the vernacular worlds, suggesting that true democratic participation requires a recovery of the cultural self.
Keywords: Socialist Realism; Postmodern Scepticism; Colonial Consciousness; Epistemic Violence; Intimate Enemy; Linguistic Democracy